Utilization of Digital Marketing by Sharia Economics Students at UIN Raden Intan in Online Business - Fida Abdurrofi; Ulil Albab; Mawardi Mawardi; Sri Choiriyati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Irresponsible individuals often misuse social media, but for university students, social media is essential, especially for online businesses. Students use derivatives from digital marketing, namely social media, which is supported by various applications for online business purposes. The methodology employed is descriptive qualitative research, and the data sources are primarily gathered through field research and supplemented by observations, interviews, and documentation. The data analysis technique used is qualitative research with a discourse analysis model. Discourse analysis primarily examines the